Low-dose BCG vaccination protects free-ranging cattle against naturally-acquired bovine tuberculosis. Issue 48 (19th November 2018) - Nugent, Graham; Yockney, Ivor J.; Cross, Martin L.; Buddle, Bryce M.
Highlights: BCG vaccine was trialled in New Zealand cattle against naturally-acquired bovine TB. We applied a five-fold lower BCG dose to cattle than any previously-used in cattle. Annual TB prevalence was low (<4%); nevertheless vaccine efficacy was significant (87.5%). Reduced BCG doses could favour cost-effective use of the vaccine in farming. Abstract: Vaccination of cattle with Mycobacterium bovis BCG has been shown to protect against infection with virulent strains of M. bovis, and against resultant bovine tuberculosis (TB). Here we report on a large-scale trial in New Zealand where free-ranging cattle were vaccinated with 3 x 10 5 BCG via injection, a lower dose than any previously trialed in cattle against exposure to a natural force of M. bovis infection. In a multi-year enrolment study involving >800 animals, three cohorts of 1–2 year old cattle were randomised to receive vaccine or to serve as non-vaccinated controls. Cattle were slaughtered and subject to standard abattoir post mortem examination for M. bovis culture-positive TB lesions after up to 3.7 years of in-field exposure; additionally, lymph node samples from approximately half of the cattle were examined further to identify infection in the absence of lesions. Overall TB prevalence, as identified by gross lesions detected at slaughter, was low among farmed cattle at the study site (<4% annually). There were two lesioned cases among 520 vaccinated trial cattle (0.38%) compared to eight among 297 non-vaccinated trial cattle (2.69%). Trial vaccine efficacy was 85.7% against abattoir-detectable TB (statistically significant protection), and 86.7% when adjusted for duration of exposure. BCG vaccination did not significantly affect the response rates of cattle to ante mortem skin- or blood-tests in diagnostic tests conducted >7 months post-vaccination. Use of a reduced, yet effective, dose of BCG would increase the cost effectiveness of using this vaccine in a bovine TB control programme.